Performance analysis of up-link and down-link mixed RF/FSO links with multiple relays - Abou-Rjeily, Chadi (2018)
This paper targets the bit error rate (BER) performance analysis of mixed radio-frequency free-space optical (RF/FSO) communication systems with a single source, single destination and multiple relays operating in the decode-and-forward (DF) mode. Several relaying scenarios are analyzed and compared for both the up-link (RF hop followed by an FSO hop) and the down-link (FSO hop followed by an RF hop). The RF links are subject to Nakagami fading and corrupted by additive Gaussian noise while the FSO links are subject to gamma-gamma scintillation where the photons generated by the background noise and dark currents follow the Poisson distribution.